Perspectives of a tailored lifestyle program for people with severe mental illness receiving housing support. Issue 2 (13th September 2017) - Rönngren, Ylva; Björk, Annette; Haage, David; Audulv, Åsa; Kristiansen, Lisbeth
Abstract: Purpose: The purpose of the present study was to describe the acceptability of the lifestyle program PHYS/CAT and to get information about the tools used for assessment of functional exercise capacity, cognitive performance, and self‐health‐related quality of life. Design and Methods: The findings are based on focus groups and the researchers' experiences of conducting the program as well as using the assessment tools. Findings: The acceptability of the program and the assessment tools was mainly satisfactory. Practice Implications: The program with relational, educational, and supportive dimensions may be a promising tool to be integrated into daily nursing care.